HUBUNGAN KONTROL ORANG TUA DENGAN ADIKSI BERMAIN GAME ONLINE PADA ANAK USIA SEKOLAH - Tri Nurmalisa Dj; Veny " Elita; Rismadefi " Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract  Online game is game that often accessed by many players using internet. The players usually can not stop playing game because find satisfaction in the game they don’t  find in real world. This research aim to determine the relationship between parenting control with playing online game addiction of school age children. This research use the correlation method with cross sectional. It is conduct on 98 parents and school age childrens who live in villages Simpang Tiga and Tangkerang Selatan sub district Bukit Raya in Pekanbaru by using purposive sampling. Data is collect using questionnaire for Lemmens with 7 addiction criteria. Responden who include to positive addiction category if they have ≥ 4 addiction criteria and negative addiction category if they have < 4 addiction criteria. The analysis use univariate and bivariate analysis using chi square. The result show that there is a relationship between parenting control with playing online game addiction of school age children with significance of 0,05 is obtained p value (0,01) <0,05 the result of this research suggest parents to increase attention and control their children in playing online game. Keyword: Addiction, online game, playing, school age children